Dual Electrochemical Methods for Determination of Anesthetic Procaine: Square Wave Voltammetry and Differential Pulse Polarography - Qadir, Gulan S.; Al-Taee, Amer T.; Othman, Nabeel S. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2024)
Procaine belongs to a type of medicine in which excessive dosage form creates cardiac problems and many allergenic reactions. Thus, continuous monitoring of this drug and its metabolite is crucial for sustainable health management during treatment. In this study, electrochemical techniques such as square wave voltammetry (SWV) and differential pulse polarography (DPP) are utilized for assaying procaine amounts in standard and pharmaceutical formulations. In SWV, the reduction of diazotized procaine gives a reduction peak at −0.05 V which is directly proportional with procaine hydrochloride concentration, whereas in DPP, the interaction of the drug with lead cation at −0.4 V is followed by the decrease in peak current of the lead cation reduction peak, which is directly proportional with the concentration of the drug. Both methods indicate high accuracy, sensitivity and precision. Linear concentration ranges of both methods are 0.0999–5.996 × 10-7 M for SWV and 0.1999–5.996 × 10-7 M for DPP. The limit of detection (LOD) and limit of quantification (LOQ) are calculated for both SWV and DPP techniques, and found that LOD equals 1.984 × 10-9 M and LOQ equals 6.611 × 10-9 M for SWV, while for (DPP) LOD and LOQ were found to be 3.519 × 10-9 M and 1.173 × 10-8 M, respectively.